2019
DOI: 10.9734/ajarr/2019/v7i130162
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effect of Moringa (Moringa oleifera) Leaf Supplemented Feed on the Growth and Carcass Quality of Broilers in Calabar

Abstract: Background: Rapid population growth of human and livestock create increasing demands for food, nutrition security in developing countries and therefore alternative feed resources must be identified and evaluated. This study was carried out to investigate the effects of Moringa oleifera leaf meal (MOLM) on supplemented feed on the growth and carcass quality of broilers in Calabar. Methodology: Fresh leaves of Moringa oleifera were bought and collected from Calabar, Nigeria. The leaves were dried for four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Similar to growth performance, the literature differs regarding the effects of dietary supplementation of Moringa on chicken carcass traits [ 51 , 52 , 53 ]. In our study, carcass weight and carcass yield were not significantly influenced by the treatments, a result that agrees with some authors [ 40 , 54 , 55 , 56 ] but contrasts with the findings of others [ 36 , 46 ]. Discrepancies between studies could be attributed to the different biological materials and diets used in each experiment, as well as the climate and environment where the trials took place, which in turn may affect both the animal performance and the Moringa composition.…”
Section: Discussionsupporting
confidence: 83%
“…Similar to growth performance, the literature differs regarding the effects of dietary supplementation of Moringa on chicken carcass traits [ 51 , 52 , 53 ]. In our study, carcass weight and carcass yield were not significantly influenced by the treatments, a result that agrees with some authors [ 40 , 54 , 55 , 56 ] but contrasts with the findings of others [ 36 , 46 ]. Discrepancies between studies could be attributed to the different biological materials and diets used in each experiment, as well as the climate and environment where the trials took place, which in turn may affect both the animal performance and the Moringa composition.…”
Section: Discussionsupporting
confidence: 83%
“…There was significant increase in dressing%, liver, spleen heart and intestinal weights by addition of 1.25, 2.4 and 3.75% M. oleifera leaf meal to broiler diets (Baloch et al, 2021). Also, Edu et al (2019) showed higher values of dressing percentage in birds fed diets with 10% M. oleifera leaf meal. Sebola and Mokoboki (2019) studied the supplementation of M. oleifera on three chicken strains and found that higher inclusion levels of Moringa leaf meal (10%) resulted in longer small intestines and heavier gizzards.…”
Section: Carcass Traitsmentioning
confidence: 90%
“…Tannins have the ability to form complex bonds with metal ions and macromolecules (protein and polysaccharides), ultimately leading to decreased nutrient bioavailability (Igwilo et al, 2010). High concentration of tannins and phytate have been seen to affect negatively the digestibility and metabolism and therefore reduced the utilization rate of dietary nutrients and can negatively influence the growth rate from one side and other side can lead to deteriorate effect on red blood cells and haemoglobin in broiler and non-ruminants as reported by (Okai et al, 1984;Esonu, 2001;Akubugwo et al, 2007;Igwilo et al, 2010;Edu et al, 2019). In addition, phytate has a strong binding affinity for calcium, magnesium, iron, copper and zinc, preventing their absorption in the gut and can negatively influence the development of skeletal and red blood cells (Falowo et al, 2018;Emiola et al, 2003;Odetola et al, 2012).…”
Section: Antinutrients In M Oleiferamentioning
confidence: 97%